2006
DOI: 10.1002/ajmg.b.30455
|View full text |Cite
|
Sign up to set email alerts
|

The 5‐HTTLPR s/s genotype at the serotonin transporter gene (SLC6A4) increases the risk for depression in a large cohort of primary care attendees: The PREDICT‐gene study

Abstract: Previous reports and meta-analyses have yielded inconclusive results as to whether the s/s genotype at the 5-HTTLPR serotonin transporter polymorphism confers increased risk for depression. We tested the association between s/s genotype and depression in a large cohort (n = 737) of Spanish primary care consecutive attendees participating in a European study on predictors for depression in primary care (PREDICT study). Participants were administered the Composite International Diagnostic Interview (CIDI) depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
4
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 31 publications
1
65
4
3
Order By: Relevance
“…Table 2 shows that depression was associated with the 5HTTLPR s/s genotype, as reported in detail elsewhere. 9 In brief, the association between the s/s genotype and depression was independent of age, sex, family history of psychological problems among firstdegree relatives and GAD, but these associations were stronger for more severe depressive episodes. Both outcomes of depression were strongly and independently associated with previous exposure to TLE with initial crude associations remaining robust after adjusting for age, gender, marital status, education and family history of psychological problems (Table 2).…”
Section: Associations With Depressionmentioning
confidence: 95%
See 3 more Smart Citations
“…Table 2 shows that depression was associated with the 5HTTLPR s/s genotype, as reported in detail elsewhere. 9 In brief, the association between the s/s genotype and depression was independent of age, sex, family history of psychological problems among firstdegree relatives and GAD, but these associations were stronger for more severe depressive episodes. Both outcomes of depression were strongly and independently associated with previous exposure to TLE with initial crude associations remaining robust after adjusting for age, gender, marital status, education and family history of psychological problems (Table 2).…”
Section: Associations With Depressionmentioning
confidence: 95%
“…The PREDICT-Gene study 9 is a case-control association study nested in a cohort of Spanish participants who were part of a larger study on prediction of onset of depression in European primary-care attendees (PREDICT study). A detailed description of the PREDICT study design and its method has been reported elsewhere.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies of whites [143][144][145][146][147] found no substantial relationships between the 5-HTTLPR genotype and major depressive disorder. In contrast, seven Caucasian [148][149][150][151][152][153][154] and one non-Ashkenazi Jewish [144] studies found that the SS genotype was associated with a modest increase in risk of depression. Furthermore, one Polish [155] and one German [156] studies found that the SS genotype was associated with a significant increase in risk of depression.…”
Section: Major Depressive Disorder and 5-httlpr Polymorphismmentioning
confidence: 99%